Unveiling the role of sintering temperatures in the physical properties of Cu-Mg ferrite nanoparticles for photocatalytic application - Sumi Akter; M.N.I. Khan; Faria Ferdous; H.N. Das; M.K. Alam; Md Abdur Rahman; Tarique Hasan; Ishtiaque M. Syed (Heliyon)
This research presents an explicit analysis of the effects of sintering temperature (Ts) on the structural, morphological, magnetic, and optical properties of Cu0.5Mg0.5Fe2O4 nanoferrites synthesized via the sol-gel method. To accomplish it, Cu-Mg ferrite NPs were sintered at temperatures ranging from 300 to 800 °C in increments of 100 with a constant holding duration of 5 h. Thermogravimetric analysis was used to observe the degradation of organic components and the thermally stable zone of the material. XRD analysis and SAED patterns revealed the formation of a single face-centred cubic (fcc) spinel structure with an Fd–3m space group. The particle's crystallite sizes have grown from 4.54 to 102.54 nm as Ts have increased, consistent with TEM results. Further evidence for the creation of spinel structure was provided by two prominent absorption bands in FTIR spectroscopy below 1000 cm−1. The particles were found to have a densely packed, nearly spherical morphology, as confirmed by TEM images. The EDS was utilized to identify the chemical species that were present in the sample. A significant correlation was observed between particle size and magnetic properties. The field-dependent magnetization investigations revealed that particles with crystallite sizes of 4.54 and 5.10 nm were superparamagnetic, while those measuring 11.68, 23.81, 42.95, and 102.54 nm exhibited ferrimagnetic characteristics. Furthermore, it was revealed that an increase in sintering temperature results in a concurrent amplification of crystallites, which subsequently heightens the saturation magnetization of the prepared NPs from 9.49 to 33.04 emu/g. The coercivity value clarifies the sintering effect of transforming the particle from a single-domain to a multi-domain magnetic state. The finite-size scaling formula precisely characterizes the changes in Curie temperature. In addition, the semiconducting characteristics of Cu-Mg ferrite NPs were confirmed through DRS, which unfolded an optical band gap within the range of 1.84–2.26 eV. The Mulliken electronegativity approach unveiled the prospective efficacy of these NPs in photocatalytically generating O2 from water. Cu-Mg nanoferrites exhibit a favourable bandgap and potential as a photocatalyst, rendering them a potentially fruitful addition to the family of ferrite materials utilized in photocatalytic and associated solar energy applications.